Пектроскопия высокого разрешения молекулы CH2=CD2: анализ «горячей» полосы ν7+ν10-ν10 - Берёзкин К. Б. Кирилл Борисович; Фомченко А. Л. Анна Леонидовна; Аслаповская Ю. С. Юлия Сергеевна; Громова О. В. Ольга Васильевна; Бехтерева Е. С. Елена Сергеевна; Мауль Г. К. Ганс Кристоф (2017, 2017)
Заглавие с экрана